Floristic novelties in the context of interdisciplinary studies - N. P. Stepanyan-Gandilyan; R. A. Hovsepyan (Труды по прикладной ботанике, генетике и селекции, 2021)
Nowa days, interdisciplinary studies are increasingly important. Integration of botany with humanities, particularly with archaeology and ethnology, is amongst these studies. It is noteworthy that, as a result of such surveys, not only “synthetic” new data could be obtained, but also data in the specific fields of knowledge that compose these multidisciplinary complexes. Thus, during the archaeo- and ethnobotanical studies in Armenia in 2017–2021, along with the data on plant resources, little-known phytonyms, etc., some new floristic data were also recorded regarding the following species: Amaranthus graecizans L., A. hybridus L., Chamaenerion angustifolium (L.) Scop., Diospyros lotus L., Eleocharis palustris (L.) Roem. & Schult., Heracleum trachyloma Fisch. & C.A. Mey., Humulus lupulus L., Hippophae rhamnoides L., Polygonatum orientale Desf., and Ranunculus lateriflorus DC. Earlier, we also procured new data on the phytogeography for such species as Crataegus × armena Pojark., Ephedra procera Fisch. & C.A. Mey., Erodium ciconium (L.) L’Hér., Leonurus cardiaca L., Leucanthemum vulgare L., Matricaria matricarioides (Less.) Porter ex Britt., Neslia paniculata (L.) Desv., Origanum vulgare L., Salvia nemorosa L., Thymus eriophorus Ronn., Th. transcaucasicus Ronn., Tripleurospermum caucasicum (Willd.) Hayek, and T. parviflorum (Willd.) Pobed. Among the species, for which phytogeographic and floristic novelties were recorded, are crop wild relatives, endemics, and rare species, included in the IUCN list. Summarizing the findings, it can be stated that archaeo- and ethnobotany are productive not only in their interdisciplinary, “hybrid” results but also in the disciplines they both synthesize. This is the evidence that interdisciplinary approaches are highly efficient for research, demonstrating a mutually enhanced, i.e., synergistic effect in complex studies.